Optimizing Academic Advising to Enhance On-Time Graduation: Effective Strategies in Higher Education Management - Toifuriah, Ahmad; Mu’arif, Mu’arif; Astuti, Ruli; Surbakti, Andika Hariyanto; Rifai, Ahmad (Universitas Nurul Jadid, 2023)
This research focuses on analyzing the effectiveness of academic guidance in supporting students' on-time graduation in higher education. The main objective of this study is to identify the factors that affect the success of academic guidance and how the interaction between academic advisors (DPAs) and students can be optimized to improve on-time graduation. This study uses a quantitative method with a descriptive approach, where data is collected through a questionnaire distributed to 31 students of the Education Management Study Program at the Faculty of Tarbiyah and Teacher Training, Syarif Hidayatullah State Islamic University Jakarta. Data analysis was carried out using descriptive and inferential statistical techniques, including Pearson correlation tests and simple regression. The results showed that academic guidance had a significant influence on students' on-time graduation, with factors such as frequency of interaction, personalized guidance, and psychological support from DPA playing an important role. Students who receive quality academic guidance are more likely to graduate on time compared to those who do not receive adequate guidance. The implications of this study emphasize the importance of developing more structured and personalized academic guidance programs in higher education, as part of education management strategies to improve the efficiency and quality of higher education